A articulação dos movimentos sociais de direita pela pauta do aborto no legislativo brasileiro - Lívia Pereira de Souza (2021)
The present work intends to understand how the right-wing social movements act in relation to the theme of abortion in the Brazilian legislature. Preliminarily, it is important to highlight that the right to abortion is the recognition of women's citizenship, through the exercise of the autonomy over their bodies. We understand that a democracy is not compatible with the denial of women's freedom. To understand how the social movements against abortion are articulated in the legislative branch of the State, at first, we will develop the question of abortion within the democratic and feminist theory, in its recognition of the autonomy of women. In the sequence, we will present the reality of abortion, focusing on Brazil, but with some compared public policies of Latin America (Argentina and Uruguay), due to our understanding that there is a setback in the reproductive rights agenda that goes beyond the Brazilian case. We ended the first part of our analysis by investigating who the actors are and what interests are at stake in the dispute over the topic. Next, we will address the Brazilian legislature and the treatment given to reproductive rights. At this point, we believe it is important to develop the issue of the rise of conservatism - which has a direct impact on abortion issues and disputes - related to our public policies. To carry out this research, we will analyze public hearings in the chamber of deputies in bills that have the object of restricting the right to abortion - who are the deputies that require the hearing, the parties and benches to which they belong, and who are the invited, which organizations are part of and which speeches they mobilize. For that, we will mobilize the methodology of textual discourse analysis and framing analysis.